Pacemaker activity and ionic currents in mouse atrioventricular node cells - Marger, Laurine; Mesirca, Pietro; Alig, Jacqueline; Torrente, Angelo; Dubel, Stefan; Engeland, Birgit; Kanani, Sandra; Fontanaud, Pierre; Striessnig, Joerg; Shin, Hee-Sup; Isbrandt, Dirk; Ehmke, Heimo; et al. (TAYLOR & FRANCIS INC, 2011)
It is well established that pacemaker activity of the sino-atrial node (SAN) initiates the heartbeat. However, the atrioventricular node (AVN) can generate viable pacemaker activity in case of SAN failure, but we have limited knowledge of the ionic bases of AVN automaticity. We characterized pacemaker activity and ionic currents in automatic myocytes of the mouse AVN. Pacemaking of AVN cells (AVNCs) was lower than that of SAN pacemaker cells (SANCs), both in control conditions and upon perfusion of isoproterenol (ISO). Block of I-Na by tetrodotoxin (TTX) or of I-Ca,I-L by isradipine abolished AVNCs pacemaker activity. TTX-resistant (I-Nar) and TTX-sensitive (I-Nas) Na+ currents were recorded in mouse AVNCs, as well as T-(I-Ca,I-T) and L-type (I-Ca,I-L) Ca2+ currents. I-Ca,I-L density was lower than in SANCs (51%). The density of the hyperpolarization-activated current, (I-to) and that of the fast component of the delayed rectifier current (I-Ks) were, respectively, lower (52%) and higher (53%) in AVNCs than in SANCs. Pharmacological inhibition of I-f by 3 mu M ZD-7228 reduced pacemaker activity by 16%, suggesting a relevant role for I-f in AVNCs automaticity. Some AVNCs expressed also moderate densities of the transient outward K+ current (I-to). In contrast, no detectable slow component of the delayed rectifier current (I-Ks) could be recorded in AVNCs. The lower densities of I-f and I-Ca,I-L, as well as higher expression of I-Kr in AVNCs than in SA NCs may contribute to the intrinsically slower AVNCs pacemaking than that of SANCs.